Effect of Date Palm (Phoenix dactylifera) Fruits Consumption on Birth Delivery Outcome: Meta-Analysis - Siwi, Ratna Purwani; Murti, Bhisma; Tamtomo, Didik (Indonesian Journal of Medicine, 2023)
Background:  The choice of cesarean section continues to increase in the world and is expected to continue to increase over the coming decades, which is almost a third of all deliveries in 2030. The benefits of dates for improving labor processes are considered to increase vaginal deliveries and also reduce the frequency of cesarean sections with the aim of reducing bigger complications. This study aims to analyze and estimate the influence of the consumption of dates on labor outcomes.Subjects and Method:  This study is a systematic review and meta-analysis with PICO, P: Pregnant women, I: consumption of dates, C: No consumption dates, O: Bishop's score, length of labor, and postpartum hemorrhage. Data collection was obtained from databases, namely: PubMed, Science Direct, Springer Link, and Google Scholar. Keywords used “date fruit” OR “date palm” OR “phoenix dactylifera” AND “labor” AND “delivery”, AND “oxytocin” AND “hemorrhage”. The inclusion criteria used were full papers in English with the design of randomized controlled trials in 20002022. This study was analyzed using RevMan 5.3 software.Results:  Meta-analysis was conducted on 4 primary studies from several countries such as Iran, Malaysia, and Saudi Arabia with a sample size of 603 pregnant women. The meta-analysis concluded that there was an effect of date consumption on cervical dilatation upon admission to the hospital (SMD= 0.73; CI 95%= 0.09 to 1.38; p=0.030). Consumption of dates also has an effect on the duration of active 1st stage labor (SMD= 0.46; CI 95%= 0.82 to 0.09; p= 0.010). Consumption of dates has a weak effect on the length of stage II labor (SMD= 0.05; 95% CI= 0.88 to 0.78; p= 0.910). In addition, the consumption of dates also has a weak effect on the length of stage III labor (SMD=0.16; CI95%=0.46 to 0.79; p=0.610).Conclusion:  Consumption of dates has an influence on labor outcomes.Keywords:  phoenix dactylifera, dates, labor, postpartum hemorrhage, Bishop scoreCorrespondence: Ratna Purwani Siwi. Masters Program in Public Health, Universitas Sebelas Maret. Jalan Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: ratnapsiwi@yahoo.com. Mobile: 085602389598.Indonesian Journal of Medicine (2023), 08(01): 79-91https://doi.org/10.26911/theijmed.2023.08.01.08